AB0930 Real-world effectiveness and safety of apremilast in german patients with psoriatic arthritis: analysis of an ongoing multicentre, prospective, non-interventional study. (12th June 2018) - Wollenhaupt, J.; Klopsch, T.; Strothmeyer, H.; Morys, S.; Bach, C.; Nunez-Gomez, N.
Abstract : Background: Apremilast (APR) has been studied extensively in phase III randomised, controlled trials. However, there is a lack of real-world evidence of effectiveness and safety in a broad population of pts with psoriatic arthritis (PsA). Objectives: To assess effectiveness and safety of APR in pts with active PsA from routine clinical practice settings in Germany. Methods: In this multicentre, prospective, non-interventional study, the primary endpoint was the proportion of pts reaching ≥1 point (≥20%) improvement from baseline (BL) in the Physician's Global Assessment of Disease Activity (PhGA) score. Other endpoints included effects on tender and swollen joint counts, psoriasis-affected body surface area (BSA), enthesitis, dactylitis, Patient's Global Assessment of Disease Activity score (PtGA), Psoriatic Arthritis Impact of Disease tool (PsAID), pain and pruritus. The current analysis is based on observed data. Results: The first 202 of a planned 500 German pts receiving APR for ≥4 month (≥1 month [V1], ≥4 month [V2]) and 127 pts receiving APR for ≥7 months (V3) were evaluated. Mean age was 54 years, mean BMI was 29 kg/m 2 and 61% were female. The mean duration of psoriasis was 25 years and of PsA was 18 years; ≈30% of pts were biologic-experienced. The mean (SD) PhGA was 2.5 (0.56) at BL. After V1, 60% of pts achieved ≥1 point improvement in PhGA, which increased to 76% (V2) and 87% (V3). Mean (SD) PhGA decreased to 1.7 (0.69), 1.4 (0.73) and 1.1 (0.74) at V1, V2, and V3 respectively. Achievement of a PhGA of 0–1 increased from 0% of pts at BL to 36.8% (V1), 65.0% (V2) and 77.2% (V3). Median improvements in tender and swollen joint counts from BL to V3 were 57.1% and 60.0%, respectively. BSA improved from 11.4% at BL to 8.3%, 5.1% and 3.5% at V1, V2 and V3, respectively. At BL, 48.4% of pts had enthesitis based on Leeds Enthesitis Index; 46% reached a score of 0 by V1, 57% by V2% and 60% by V3. At BL, 27.3% of pts had dactylitis; a score of 0 was achieved by 40.0%, 66.7% and 71.9% of pts by V1, V2, and V3, respectively. BL mean PsAID score (5.33; max=10.00) decreased to 4.40 (V1), 3.85 (V2) and 3.36 (V3). Improvements were also seen in PtGA, overall pain and pruritus. A sub-analysis suggests that APR was associated with greater benefits in biologic-naive pts compared with pts who previously received biologic therapies. The observed safety and tolerability after V3 was consistent with the known overall safety profile of APR. Common AEs in clinical trials were similar, with a lower incidence: diarrhoea (10.4%), nausea (5.6%), headache (4.0%), and respiratory tract infection (1.2%). Conclusions: The first results from this real-world PsA study reinforce findings from previous clinical trials of APR. In pts with ≥4 and≥7 months of follow-up, APR was associated with improvements in both physician-assessed and patient-reported outcomes, with possibly a greater benefit in biologic-naïve compared with biologic-experienced pts. Safety and tolerability were similar to the known profile of APR. Disclosure of Interest: J. Wollenhaupt Grant/research support from: Celgene Corporation, T. Klopsch: None declared, H. Strothmeyer: None declared, S. Morys Employee of: Celgene GmbH, C. Bach Employee of: Celgene GmbH, N. Nunez-Gomez Employee of: Celgene GmbH